(untitled) - Shusterman, Neal (Simon & Schuster Books for Young Readers, 2018)
Rowan and Citra take opposite stances on the morality of the Scythedom, putting them at odds, and the Thunderhead is not pleased.
Keywords: Death; Juvenile fiction; Murder; Juvenile fiction; Death; Fiction; Murder; Fiction; Science fiction; Science fiction